Intestinal colonization with ESBL-producing Klebsiella pneumoniae in healthy rural villager: A genomic surveillance study in China, 2015-2017 - Wang, Shuang; Xie, Hengjie; Chen, Yuzhen; Liu, Lu; Fang, Ming; Sun, Dapeng; Xu, Liuchen; Bi, Zhenqiang; Sun, Gaoxiang; Li, Yan; Yu, Xiaolin; Zhang, Huaning; et al. (Frontiers in Public Health, 2022)
The worldwide emergence and diffusion of extended-spectrum β-lactamase producing-Klebsiella pneumoniae (ESBL-KP) are particularly concerned. However, comprehensive studies addressing the intestinal colonization with ESBL-KP in healthy rural villager are scarce. Here we investigated the epidemiological and etiological characteristics of ESBL-KP in faecal samples from healthy persons in rural communities in Shandong Province, China, from 2015 to 2017. ESBL-KP carriage increased from 12.0% in 2015 to 27.5% in 2017. The experimental results showed that 97% of isolates had multi-drug resistance. Multiple ESBL resistance genotypes were commonly detected in the isolates. STs among the ESBL-KP isolates were diverse, with the high-risk clone ST101 as the dominant clone. All 69 blaCTX-M-3-positive isolates were located on plasmids, and these genes could be transferred with plasmids between different strains. Phylogenetic analysis showed the possibility of transmission among some isolates. In this study, we report a sharp rise in the prevalence of ESBL-KP among faecal samples collected from healthy rural residents of Shandong Province from 2015 to 2017, and showed the high endemicity of CTX-M producers. The carrier rate of multidrug-resistant bacteria in healthy residents is increasing. Thus, a need for further monitoring and possible interventions to reduce the spread of ESBL-KP in this region is warranted.